Elastohydrodynamic film thickness of soft EHL contacts using optical interferometry - Marx,N; Guegan,J; Spikes,HA (Tribology International, 2016)
Robust, chromium, semi-reflective coatings have been applied to transparent polymethylmethacrylate and polyurethane discs and this has enabled conventional, normal incidence optical interferometry to be used to measure lubricant film thickness in soft EHL conditions for the first time. High quality interferograms comparable to those obtained from coated glass discs are obtained. Measured film thickness has been compared with existing soft EHL film thickness equations obtained using computer modelling and revised central and minimum film thickness equations have been proposed. These film thickness measurements and measurement technique have applicability to our understanding of the performance and design of lubricated gears and bearings manufactured from polymeric materials.